Multimolecular characteristics and role of BRCA1 interacting protein C-terminal helicase 1 (BRIP1) in human tumors: a pan-cancer analysis - Ruohuang Wang; Jisheng Zhang; Xin Cui; Shun Wang; Ting Chen; Yanfang Niu; Xiaoyun Du; Jingwen Kong; Lin Wang; Yan Jiang (World Journal of Surgical Oncology, 2023)
Abstract Background The aberrant expression of BRIP1 was associated with several cancers; however, the panoramic picture of BRIP1 in human tumors remains unclear. This study aims to explore the pan-cancerous picture of the expression of BRIP1 across 33 human cancers. Methods Based on the data from TCGA and GTEx, a series of bioinformatic analyses were applied to systematically explore the genetic landscape and biologic function of BRIP1 in 33 human tumors. Results We observed prognosis-related differential BRIP1 expressions between various carcinomas and the corresponding normal tissues. “Basal transcription factors,” “homologous recombination,” “nucleotide excision repair,” and DNA metabolism pathways may play a role in the functional mechanisms of BRIP1. Patients with uterine corpus endometrial carcinoma presented with the highest alteration frequency of BRIP1 (nearly 10%). Single-nucleotide and copy number variations of BRIP1 were noticed in multiple cancers, and the expression of BRIP1 is significantly regulated by copy number variation in breast invasive carcinoma and lung squamous cell carcinoma. BRIP1 expression is negatively correlated with the DNA methylation levels in many tumors and is associated with the activation of apoptosis, cell cycle, DNA damage response, and inhibition of hormone ER and RNS/MARK signaling pathways. Moreover, a positive correlation was observed between BRIP1 expression and the immune infiltration levels of cancer-associated fibroblasts and CD8+ T cells in lung adenocarcinoma. Conclusion Our pan-cancer analysis of BRIP1 provides a valuable resource for understanding the multimolecular characteristics and biological function of BRIP1 across human cancers.